Enhanced structure for discrete and remote L-band erbium-doped fiber amplifiers - Md. Yusoff, Nelidya (2013)
The growth of data traffic and Internet forces the telecommunication window to widen up in order to accommodate the increasing number of channels in wavelength division multiplexing network systems. This however requires wide bandwidth optical amplifiers with flat gain spectrum for multiwavelength signals to propagate simultaneously. Unfortunately, the accumulation of attenuation inside the fiber (0.2 dB/km) restricts the accessible distance of the transmitted signal and thus, causes the system performance to drop tremendously. Erbium-doped fiber amplifier (EDFA), which is able to boost the transmitted signal for longer communication distance at low pump power with significant wideband gain, is identified as an alternative to overcome the drawbacks caused by the electronic repeaters. This research work focuses on designing and developing two different structures of L-band EDFA which are discrete and remote. A flat L-band gain response is the main target in both designs with high gain, low noise figure (NF) and high optical signalto-noise ratio. For discrete L-band EDFA, the research concentrates on designing and developing a dual-stage EDFA where a new pumping scheme utilizing distributed pumping concept is introduced. This pumping scheme uses power coupler to distribute the pump power between two different amplifier stages with different lengths of erbium-doped fiber. Optimizations of the splitting ratios, erbium doped fiber lengths and pump power are required in order to achieve better performance over the Lband region. This dual-stage EDFA utilizing distributed pumping scheme offers gain and NF improvement of 1.2 dB and 5 dB respectively with better gain flatness of less than 0.4 dB when compared with the conventional single-stage EDFA. As conclusion, this dual-stage EDFA utilizing distributed pumping scheme is cost efficient as it only implements a single pump laser in the design and it does not require any gain equalizing filter to attain a reasonably flat gain response over the entire L-band region. For the other amplifier structure, the work focuses on designing and developing a remotely pumped EDFA (R-EDFA) that works at low pump power and at the same time has the ability to compensate dispersion. Due to attenuation and scattering effects that occur in the transmission fiber, a reduced 1497 nm Raman pump power is delivered to pump the R-EDFA. The presence of Raman effects in the L-band wavelength range helps to boost up the propagated signal for higher transmission gain and optical signal-to-noise ratio at the output of the proposed R-EDFA. L-band multiwavelength dispersion compensation module is used as signal reflector to form a double-pass amplifier structure and also as dispersion compensator. The work successfully demonstrates that the gain and NF are improved by 5.55 dB and 4.03 dB respectively with 4.24 dB gain flatness in comparison to conventional R-EDFA. In addition, the proposed amplifier also has the ability to compensate overall dispersion in the transmission fiber.